Prevalence of night eating syndrome associated with psychological disorders among university students: A metaanalysis - Mohammad Miraj; Faizan Kashoo; Shakir Saleem; Msaad Alzhrani; Ahmad Alanazi; Hosam Alzahrani; Mohammad Abu Shaphe; Mehrunnisha Ahmad; Fuzail Ahmad; Abdul Rahim Shaik; Ahmed Almansour; Mohamed Sherif Sirajudeen; et al. (Journal of King Saud University: Science, 2022)
The objective of this meta-analysis was to find out the prevalence of Night Eating Syndrome (NES) associated with psychological disorders among university students. Extensive search of database yielded 1541 articles matching the search keywords, out of which were 1528 were excluded due to difference in population, outcome, and study design. At the end, only 13 articles were retrieved which aligned with the inclusion criteria. Prevalence of NES associated with psychological disorders in 9432 participants was 8.2% (95% CI 4.9: 13.4) but there was high level of heterogeneity. Female university students had a higher prevalence of the disorder (7.2%) with a high degree of heterogeneity (τ2 = 0.687, I2 = 96%, P < 0.01), as compared to male students (4.9%) with lower heterogeneity. Nevertheless, high level of clinical heterogeneity was observed in this metanalysis which mandates more real-world studies with larger samples to validate the causal relationship.